Elections without order : - Rose, Richard (Cambridge University Press, 2002)
Russians want free elections and order. Although their political elites have had no difficulty in supplying candidates and parties in the last decade, predictability in everyday life and the rule of law have suffered. This book is about Russia's attempt to achieve democratization backwards, by holding elections without having created a modern state. This dilemma is the challenge that Russia presents to Vladimir Putin.